1999
DOI: 10.1007/s11661-999-0035-7
|View full text |Cite
|
Sign up to set email alerts
|

A study on laser sintering of Fe-Cu powder compacts

Abstract: The sintering of Fe-Cu powder compacts by laser beams was studied to determine densification and microstructural development. The influence of processing variables such as Cu content, laser output power, sintering time, and green density on the densification and Brinell hardness (HB) were analyzed, and several temperature curves measured during laser sintering (LS) were also discussed in this article. After LS, the samples exhibited considerable shrinkage, which was very different from the effects of conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Carbon has high solubility in Fe at temperatures above 910°C. The diffusion of carbon into iron increases the dihedral angle and thereby inhibits swelling brought about by the penetration of the Cu melt into the Fe grain boundary [13]. In this investigation, there were many reasons standing behind the swelling of the sintered compacts.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Carbon has high solubility in Fe at temperatures above 910°C. The diffusion of carbon into iron increases the dihedral angle and thereby inhibits swelling brought about by the penetration of the Cu melt into the Fe grain boundary [13]. In this investigation, there were many reasons standing behind the swelling of the sintered compacts.…”
Section: Discussionmentioning
confidence: 82%
“…It was found that sintering additives which are insoluble in W can segregate to the W interparticle zones and provide a high diffusivity transport path for W atoms which in turn leads to low activation energy for diffusion and bulk transport of the W element [9]. However many previous studies showed that swelling increases in compacts contain lower copper contents [10,11,13]. In homogenous mixtures, swelling occurs only when copper content is lower than certain value.…”
Section: Discussionmentioning
confidence: 99%
“…Fe-Cu powder mixture is one of the first selections for manufacturing of complicated shape and prototypes due to its suitable properties such as high corrosion resistance and superior mechanical properties [30,31]. Schueren and Kruth studied sintering of the Fe-Cu powder mixture and reported that the powder deposition highly depends on the powder properties [32].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that this method cannot sinter large materials because input heat by laser is not enough [6]. In order to overcome this weakness, reactive laser sintering is developed in this study, which uses reactive powders in substituted raw powder compacts [7,8].…”
Section: Introductionmentioning
confidence: 99%